High-Yield WS2 Synthesis through Sulfurization in Custom-Modified Atmospheric Pressure Chemical Vapor Deposition Reactor, Paving the Way for Selective NH3 Vapor Detection - Malik, Shuja Bashir; Annanouch, Fatima Ezahra; D′Souza, Ransell; Bittencourt, Carla; Todorović, Milica; Llobet, Eduard (American Chemical Society, 2025)
Nanostructured transition metal dichalcogenides have garnered significant research interest for physical and chemical sensing applications due to their unique crystal structure and large effective surface area. However, the high-yield synthesis of these materials on different substrates and in nanostructured films remains a challenge that hinders their real-world applications. In this work, we demonstrate the synthesis of two-dimensional (2D) tungsten disulfide (WS2) sheets on a hundred-milligram scale by sulfurization of tungsten trioxide (WO3) powder in an atmospheric pressure chemical vapor deposition reactor. The as-synthesized WS2 powders can be formulated into inks and deposited on a broad range of substrates using techniques like screen or inkjet printing, spin-coating, drop-casting, or airbrushing. Structural, morphological, and chemical composition analysis confirm the successful synthesis of edge-enriched WS2 sheets. The sensing performance of the WS2 films prepared with the synthesized 2D material was evaluated for ammonia (NH3) detection at different operating temperatures. The results reveal exceptional gas sensing responses, with the sensors showing a 100\% response toward 5 ppm of NH3 at 150 °C. The sensor detection limit was experimentally verified to be below 1 ppm of NH3 at 150 °C. Selectivity tests demonstrated the high selectivity of the edge-enriched WS2 films toward NH3 in the presence of interfering gases like CO, benzene, H2, and NO2. Furthermore, the sensors displayed remarkable stability against high levels of humidity, with only a slight decrease in response from 100\% in dry air to 93\% in humid environments. Density functional theory and Bayesian optimization simulations were performed, and the theoretical results agree with the experimental findings, revealing that the interaction between gas molecules and WS2 is primarily based on physisorption.